Performance Evaluation of Various Cluster based OFDM Schemes (International Journal of Engineering and Computer Science, 2015)
As more and more people started using the communication equipments, the demand for high data rate increases quickly. Orthogonal Frequency Division Multiplexing (OFDM) is one of the latest modulation techniques used in order to combat the frequency-selectivity of the transmission channels, also achieves high data rate without inter-symbol interference. The basic principle of OFDM is gaining a wide spread popularity within the wireless transmission community. This paper deals with the communication system that uses BPSK, QPSK and QAM techniques to transmit information using OFDM technique over Rayleigh communication channel. In terms of Symbol Error Rate (SER), the performance of different modulation schemes using OFDM techniques in Rayleigh channel is analyzed. For different types of modulation schemes (BPSK, QPSK, 16-QAM, 64-QAM) has been used with OFDM techniques. In this paper we analyze the Bit Error Rate (BER) of Rayleigh Fading Channels in OFDM systems using BPSK, QPSK and QAM Modulation Schemes.